Sem candura nas palavras: Clóvis Moura e os dilemas intelectuais do antirracismo no Brasil (1959-1995) - Andrade, José Maria Vieira de (2019)
In this thesis, we approach some fragments of the intellectual trajectory of Clovis Steiger de Assis Moura (1929-2003) as a pretext to reflect on some transformations that occurred with antiracist thinking in Brazil, in the second half of the 20th century and in the first decades of the 21st century. Considering that this is one of the most active names in this period, we wonder, particularly, how the "effort of conformation" (Schwarz, 1993) operationalized by the writer, in relation to the notions of intelectual and black identity, helps us to understand the process of racialization that occurred with black activism between the late 1950s and the early 1990s. We analyze this issue in Moura's extensive intellectual production, both in his most recurring works - chapters, books and articles in periodicals - and in other sources not very known yet, such as personal correspondence and some books of poetry by the writer. Through this material, we point out that polarizing and generalizing categorizations - such as those that currently subdivide the antiracist debate between "racial studies" on the one hand, and "their critics" on the other hand (COSTA, 2006) - do not seem to cope with the complexity and heterogeneity of Moura's. The links and mismatches of his essayistic /activist and poetic production help us to understand the paradoxical relation that the author maintained with the notion of black identity as a strategy to fight against racism, as well as with the conception of intellectual and written engagement that permeates part of black activist thinking.